STRATEGI PEMERTAHANAN SENI LUKIS WAYANG KACA DESA NAGASEPAHA - I Putu Ardiyasa; Komang Yunitri Rahayu (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
The Art of Wayang Kaca Painting in Nagasepaha Village lives through various developments and changes in the supporting community. Since 1927-present, this art is still alive in the ritual community and exhibition space, but the sustainability of this native art of North Bali has not been supported by regeneration and revitalization to the fullest. This study aims to find an offer that can solve problems in the Wayang Kaca painting ecosystem using a qualitative approach. Data Collected through Observations, Interviews, and Documentation studies of related research. The results show that the Nagasepaha Glass Wayang Painting can read the times, quality works, from the heart, build and maintain relationships, regenerate artists, empower public spaces and digital media.Keyword :Art and Culture, Naga Sepaha Wayang Kaca Painting